Pharmacotherapy Challenges of Fontan‐Associated Plastic Bronchitis: A Rare Pediatric Disease. Issue 9 (17th May 2013) - Brooks, Kristina; Caruthers, Regine L.; Schumacher, Kurt R.; Stringer, Kathleen A.
Abstract : Pediatric pharmacotherapy is often challenging due to the paucity of available clinical data on the safety and efficacy of drugs that are commonly used in children. This quandary is even more prevalent in children with rare diseases. Although extrapolations for dosing and administration are often made from available adult data with similar disease states, this translation becomes even more problematic in rare pediatric diseases. Understanding of rare disease pathophysiology is typically poor, and few, if any, effective therapies have been studied and identified. One condition that illustrates these issues is plastic bronchitis, a rare, most often pediatric disease that is characterized by the production of obstructive bronchial airway casts. This illness primarily occurs in children with congenital heart disease, often after palliative surgery. Plastic bronchitis is a highly clinically relevant and therapeutically challenging problem with a high mortality rate, and, a generally accepted effective pharmacotherapy regimen has yet to be identified. Furthermore, the disease is ill defined, which makes timely identification and treatment of children with plastic bronchitis difficult. The pharmacotherapies currently used to manage this disease are largely anecdotal and vary between the use of macrolide antibiotics, mucolytics, bronchodilators, and inhaled fibrinolytics in a myriad of combinations. The purpose of this review is 2‐fold: first, to highlight the dilemma of treating plastic bronchitis, and second, to bring attention to the continuing need for studies of drug therapies used in children so safe and effective drug regimens can be established, particularly for rare diseases.